A distinctive new species of moss salamander (Caudata: Plethodontidae: Nototriton) from an imperiled Honduran endemism hotspot - Townsend, Josiah H.; Butler, J. Michael; Wilson, Larry David; Austin, James D. (Zootaxa, 2010)
A new species of Nototriton is described from Refugio de Vida Silvestre Texiguat in northern Honduras, and is presented in a new phylogenetic hypothesis for the genus Nototriton. This species differs from all other congeners by a number of morphological characteristics, including but not limited to large nares, syndactylous hands and feet with pointed toe tips, and a pale ventral surface with light mottling. Mitochondrial sequence divergence distinguishes this species from all other Nototriton (3.6–6.0% at 16S and 10.2–15.1% at cytochrome b). Refugio de Vida Silvestre Texiguat harbors a remarkable herpetofauna, including 20% of all endemic amphibian and reptile species in Honduras, among which are five species (one anuran, one lizard, and three snakes) known only from the immediate vicinity of the type locality of the new species. Despite the evolutionary and conservation importance of this reserve, it remains one of the most imperiled cloud forests in Honduras due to persistent illegal logging and forest clearing.